Implementation of an electronic patient portal in routine mental health care of hospitals in Germany - evaluation of attitudes of healthcare providers - Isabelle Reinhardt; Rosa Holsten; Jürgen Zielasek; Laura Kuhlmann; Euphrosyne Gouzoulis-Mayfrank (BMC, 2024)
Abstract Background The use of digital tools such as electronic patient portals in different health care disciplines and settings has been increasing, but the rate of implementation in clinical practice still lags behind expectations. While studies have linked the use of electronic patient portals to positive health outcomes for patients, studies addressing the viewpoints of healthcare providers are rare. Methods We performed an online survey of attitudes of healthcare providers towards an electronic patient portal for mental health hospitals. The portal was developed by five communal providers of mental health care in different regions in Germany. The survey was carried out during the early phase of implementation of the portal. Results Twenty project leaders and 37 clinicians from five different mental health hospitals answered the questionnaire (response rate: 45% and 28%). Overall, acceptance of online applications among respondents was high. The healthcare providers mentioned perceived benefits (e.g. accessibility of new patient groups, use of therapy-free periods) as well as a number of technical, structural, organizational and staffing barriers for successful implementation in hospital settings (e.g. workload of healthcare providers and lack of staff, limited digital competences, unstable WLAN). Conclusion The perceived barriers and facilitators of the implementation of online applications and electronic patient portals in mental health hospitals identified by healthcare providers may be taken into account. Improving commitment of the healthcare providers to implementation and use of digital interventions may help foster digitalisation in mental health hospitals.